2008
DOI: 10.1523/jneurosci.3589-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic and Neuroendocrine Effects of Goldfish Pheromones

Abstract: Goldfish (Carassius

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 71 publications
0
22
0
Order By: Relevance
“…Real-time quantitative PCR was performed using the TaqMan MGB system (Applied Biosystems) as described previously (49). Synthetic oligos were used as standards.…”
Section: Methodsmentioning
confidence: 99%
“…Real-time quantitative PCR was performed using the TaqMan MGB system (Applied Biosystems) as described previously (49). Synthetic oligos were used as standards.…”
Section: Methodsmentioning
confidence: 99%
“…Immunostaining for noradrenaline (NA) and uncoupling protein (UCP) followed methods described previously (Chung-Davidson et al, 2008). Negative controls (deprived of the NA or UCP antibody) were performed simultaneously in every immunostaining experiment.…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…Real-time quantitative PCR (RT-qPCR) was performed using the TaqMan MGB system (Life Technologies, Carlsbad, CA, USA) as described previously (Chung-Davidson et al, 2008). Briefly, total RNA was extracted using TRIzol Reagent (Invitrogen, Carlsbad, CA, USA), treated with the TURBO DNA-free kit (Applied Biosystems, Foster City, CA, USA) and diluted to 100ngμl …”
Section: Real-time Quantitative Pcrmentioning
confidence: 99%
“…Therefore, PGF 2 á also plays a dual role as a para hormone and hormone, synchronising male and female sexual behavior in Cyprinus carpio. Davidson et al, 2008 have found that exposure to water borne PGF 2 increased neurogenesis and GnRH concentration in male goldfish brain and modulate brain plasticity associated with behavioral changes during spawning season via the neuroendocrine (GnRH) and motor components of the pheromone-reproductive system. This finding confirms the above view in C. carpio in relation with increased number of gonadotrops, olfactory secretion.…”
Section: Discussionmentioning
confidence: 99%
“…In fish, exogenous prostaglandins also show stimulatory effect on the induction of ovulation. F prostaglandins also function as a hormone that stimulates female sexual behavior (Sorensen et al, 1988;Davidson et al, 2008). It is now cleared that this compound is also functioning as potent olfactory stimulants with pheromonal activity in human (Karl et al, 2005) and for many species of fish (Sorensen and Goetz, 1993).…”
Section: Introductionmentioning
confidence: 99%